ملامح الدراسة البينية عند علماء اللغة العرب - مبدوعة, كريمة (University of Eloued جامعة الوادي, 2024)
أثبت علماء العرب قصب السّبق في مجال الدّراسات التّفاعليّة بين مختلف العلوم والتّخصّصات بين مختلف الأجناس والثّقافات، فنجد تفاعل بين الطّب والأدب، بين الفلسفة والخطابة، بين الميادين العلميّة ومختلف الأجناس الأدبيّة، حتى في مصنفات كبار اللّغويين كـ: "الجاحظ"و"الجرجاني" و"الخليل" و"سيبويه" بنوا أفكارهم وعلومهم على أسس بينيّة محصّنة،لأنهم أدركوا أنه لا يوجد فكر إلا في علاقته بفكر آخر في رؤية تفاعليّة حركيّة.لم يكن التّراث العربي بمعزل عن هذه الإستراتيجيّة، هؤلاء أسهموا في بناء الفكر البيني قديمان وأكّدوا أنّ ملتقى التّخصصات ليس اكتشافا حديثا بل كان منذ أقدم العصور في تاريخ العلوم والفنون والآداب، وهو يمثل مرحلة من مراحل الإبداع، وقد حاولنا في هذه الورقة أن نسلّط الضّوء على أهميّة مفهوم البينيّة أوّلا، ثم نركّز على أهم تجلّيات الفكر البيني في التّراث العربي. ArabArabscholars have proventheir leadership in the field of interactive studiesbetweenvarious sciences and specializationsbetweendifferent races and cultures. Wefind interaction betweenmedicine and literature, betweenphilosophy and rhetoric, betweenscientificfields and variousliterary genres, even in the works of greatlinguistssuch as: “Al-Jahiz,” “Al-Jurjani,” and “Al-Jarjani.” Al-Khalil and Sibawayh builttheirideas and sciences on solidinterconnectedfoundations, becausetheyrealizedthatthereis no thoughtexcept in itsrelationship to anotherthought in an interactive, kinetic vision. The Arabheritagewas not isolatedfromthisstrategy. Theseancient people contributed to building the interdisciplinarythought and confirmedthat the meeting of specializationsis not a recentdiscovery, but ratherit has existedsinceancient times in the history of sciences, arts and literature, and itrepresents a stage of creativity, and we have triedin thispaper to shed light on The importance of the concept of inter-connectivity first, thenwe focus on the most important manifestations of inter-thought in Arabheritage.
مقال. مجلة علوم اللغة العربية وآدابها. مج07 . ع.02. جامعة الوادي
Keywords: البينية، التراث العربي، الجاحظ، الجرجاني، ابن المقفع.